Gestational Outcome in Rats That Consumed Aqueous Extract of Hibiscus sabdariffa During Pregnancy - Iyare, E.E.; Adegoke, O.A. (Pakistan Journal of Nutrition, 2011)
The present study was designed to investigate the effect of consumption of aqueous extract of litter size and birth weight (HS) during pregnancy on fluid and food intake, weight gain during pregnancy, length of gestation, litter size and birth weight. Eighteen in-bred virgin female Sprague-Dawley rats aged between 10-12 weeks and weighing 125 ± 5.5g (mean ± SEM) with two consecutive regular 4-day estrus cycle were used for this study. These rats were randomly assigned to one of three groups on gestational day one. Group A (control) were given tap water to drink throughout pregnancy, while groups B and C were given 0.6g-extract/100ml and 1.8g-extract/100ml respectively to drink throughout pregnancy. All groups had normal rat chow and their respective drinking solution ad libitum. Mean fluid and food intake and total pregnancy weight gain were significantly reduced in the HS group. There was no significant difference in length of gestation among the various groups but there was a significant reduction in litter size and a significant increase in litter birth weight in HS groups (B and C) compared with control group (A). There were no apparent malformations at birth.